The researcher's toolkit the complete guide to practitioner research - Wilkinson, David 1970-; Dokter, Dennis
"Designed for those undertaking research for the first time, this fully updated edition of The Researcher's Toolkit is a practical and accessible guide for all those partaking in small-scale research. Jargon-free and assuming no prior knowledge, it covers the entire research process, from defining a research topic or question through to its completion. This second edition has been fully revised by a collaborating team with a wealth of knowledge and practical experience in research project work. Including activity boxes to highlight key concepts and short summary boxes to indicate fundamental elements of various research areas, the chapters cover: the importance of research and framing your research question and research ethics, practical elements associated with planning and executing your research activity, the application of survey-based research methods and the value provided by social media as data collection devices, deploying both quantitative and qualitative tools and techniques to analyse research data, writing up your research work and preparing it for wider access and consumption, and examining the effect of your research work through assessing or measuring its impact. The Researcher's Toolkit is a must-read guide for students and budding researchers as well as educators seeking to explain academic research and writing to their pupils. It will benefit anyone looking to complete a research project whether inside academia or beyond"--